Governmental policy instruments to support regional physical education and sports sector - Rapoport, L. A..; Markova, A. S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze efficiency of the governmental policy instruments to support progress of the regional physical education and sport sector, with the Sverdlovsk Oblast taken for the case study. Methods and structure of the study. We analyzed, for the purposes of the study, standard Statistical Reporting Forms No. 1-FC, 5-FC, 3-AFC and 2-GTO; public information data flow of the Sverdlovsk Oblast Ministry of physical education and sport; and the relevant legal, regulatory, policy-setting and progress management policy documents of the regional Sverdlovsk Oblast physical education and sport sector control agency for the period of 2010 through 2020. Results and conclusion. We analyzed in the study the following regional governmental policy instruments proved effective for the physical education and sport sector support and advancement purposes: Analyses of the physical education and sport sector progress statistics including the sector staffing; sector financing by the progress vectors; progress statistics of the local social-needs-centered non-profit organizations; progress statistics of the All-Russian GTO Complex in the region; and reports of the SF operations with the design service capacities versus the actual attendance statistics: